Isothiocyanates: Translating the Power of Plants to People. Issue 18 (26th March 2018) - Palliyaguru, Dushani L.; Yuan, Jian‐Min; Kensler, Thomas W.; Fahey, Jed W.
Abstract: Isothiocyanates from cruciferous vegetables have been studied extensively in cells and in animals for their disease preventive and therapeutic effects. However, translating their utility to human populations has been both limited and challenging. Herein, clinical trials employing two isothiocyanates, sulforaphane (SFN; 1‐isothiocyanato‐4‐(methylsulfinyl) butane) and phenethyl isothiocyanate (PEITC; 2‐isothiocyanatoethylbenzene) that are isolated principally from broccoli and watercress, respectively, are summarized and discussed. Both of these compounds have been used in small human clinical trials, either within food matrices or as single agents, against a variety of diseases ranging from cancer to autism. Results suggest an opportunity to incorporate them, or more likely preparations derived from their source plants, into larger human disease mitigation efforts. The context for the applications of these compounds and plants in evidence‐based food and nutritional policy is also evaluated. Abstract : Broccoli and watercress are two vegetables that are rich producers of the isothiocyanates sulforaphane and phenethyl isothiocyanate, respectively. In this review, the pharmacology of these isothiocyanates is discussed and clinical trials using these plants or their bioactive compounds are summarized. Gaps in research as well as new technologies and evidence‐based food policies are also identified so that isothiocyanate research can be effectively implemented into improving human health.